2002
DOI: 10.1046/j.1365-2109.2002.00757.x
|View full text |Cite
|
Sign up to set email alerts
|

Nutritive value of palm kernel meal pretreated with enzyme or fermented withTrichoderma koningii(Oudemans) as a dietary ingredient for red hybrid tilapia (Oreochromissp.)

Abstract: The aim of this study was to evaluate whether pretreatment of palm kernel meal (PKM) with a commercial feed enzyme (Allzyme Vegpro ) or solid-state fermentation of PKM with the cellulolytic fungus Trichoderma koningii (Oudemans) could improve the nutritive value of raw PKM in the diets of red hybrid tilapia, Oreochromis sp. Seven isonitrogenous (30% crude protein) and isoenergetic (15.1 kJ g À1 ) practical diets were formulated and fed close to apparent satiation to triplicate groups of 14 fish (mean initial w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
1
6

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 23 publications
3
32
1
6
Order By: Relevance
“…Carter et al (1994) avaliaram o efeito de dieta à base de farinha de soja, suplementada com complexo multi-enzimático (tripsina, protease alcalina, protease ácida, amiloglucosidase, amilase e celulase) para o salmão do Atlântico (Salmo salar L.), concluindo que houve aumento no crescimento e na eficiência da conversão alimentar. Ng et al (2002) avaliaram o miolo de palma (PKM) da Malásia, após pré-tratamento com complexo enzimático comercial (Allzyme Vegpro) 1 6 1 1 6 1 1 6 1 VOL. 37(1) 2007: 157 -164 SILVA et al…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Carter et al (1994) avaliaram o efeito de dieta à base de farinha de soja, suplementada com complexo multi-enzimático (tripsina, protease alcalina, protease ácida, amiloglucosidase, amilase e celulase) para o salmão do Atlântico (Salmo salar L.), concluindo que houve aumento no crescimento e na eficiência da conversão alimentar. Ng et al (2002) avaliaram o miolo de palma (PKM) da Malásia, após pré-tratamento com complexo enzimático comercial (Allzyme Vegpro) 1 6 1 1 6 1 1 6 1 VOL. 37(1) 2007: 157 -164 SILVA et al…”
Section: Resultsunclassified
“…Enzimas também têm sido utilizadas com o objetivo de incorporar matérias primas de menor qualidade às rações de animais domésticos (Nery et al, 2000) e peixes (Ng et al, 2002), propiciando menor impacto causado por dejetos e aproveitamento de ingredientes disponíveis a cada região.…”
Section: Introductionunclassified
“…This suggests that at least three main cellulolytic and hemicellulolytic enzymes are needed to digest the glycosidic bonds of mannan, cellulose, and xylan to improve the nutritive value of PKE if it is to be used more efficiently in diets for poultry and other monogastric animals. Previous studies in Malaysia (Ng et al 2002;Saenphoom et al 2011) showed that commercial enzymes could be used to pre-treat PKE to degrade these fibrous compounds to usable monosaccharides to enhance their metabolizable energy before feeding them to fish and poultry. However, most of the enzymes tested were imported and not specifically designed to break down the lignocellulosic components in PKE (Ibrahim 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Os resultados encontrados estão de acordo com os obtidos por Ng et al (2002), que avaliaram o efeito do pré-Tabela 2 -Coeficientes de digestibilidade aparente da MS, PB e da EB de juvenis de tilápia-do-nilo alimentados com dietas suplementadas com níveis crescentes de complexo enzimático tratamento do farelo de miolo de palma (PKM) com complexo enzimático comercial (Allzyme Vegpro™) e observaram melhora na digestibilidade de MS, proteína, lipídeo e energia em tilápia-vermelha (Oreochromis sp.). A influência da fibra no desempenho de peixes é ainda pouco estudada e pode estar relacionada à sua composição percentual em celulose, hemicelulose, lignina e sílica, entre outros .…”
Section: Resultsunclassified